Accounting Systems, Human Resource Competence, and Transparency in Islamic Firms: Impact on Financial Reporting Quality and Stakeholder Trust - R. Ait Novatiani; Rima Rachmawati; Evi Octavia (Department of Public Administration, 2026)
This study examines how accounting information systems (AIS) and human resource competence (HRC) shape transparency and, in turn, financial reporting quality (FRQ) and stakeholder trust in Islamic firms. Grounded in agency, stakeholder, and Islamic accountability perspectives, the model positions transparency as a mechanism translating internal capabilities into credible reporting and relational legitimacy. Data were collected through a cross-sectional questionnaire survey of 148 key informants from 37 Islamic firms and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that AIS and HRC positively influence transparency, transparency improves FRQ, and both FRQ and transparency increase stakeholder trust. Bootstrapped indirect effects support the mediating role of transparency in the AIS/HRC–FRQ relationships and confirm a significant serial mediation pathway from AIS and HRC to trust through transparency and FRQ, suggesting partial mediation. By showing that trust is built through openness and information quality, the study clarifies why system upgrades or training may fail when disclosure practices remain weak or inconsistent. These findings extend prior FRQ research by integrating transparency and stakeholder trust as outcomes aligned with amanah, sidq, and adl. Practically, Islamic firms should invest in integrated AIS, competency development, disclosure SOPs, and standardized Sharia-related reporting to strengthen credibility and stakeholder confidence.